2016
DOI: 10.5812/ijpbs.4158
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy, Cognitive Emotion Regulation and Clinical Symptoms in Females With Breast Cancer

Abstract: Background: Cancer is one of the most serious chronic diseases and risk factors for population health. Breast cancer is the most common cancer diagnosed in females. Today, some researchers in the field of clinical psychology by the implementation of psychosocial interventions sought to examine these effects on psychopathology in patients with breast cancer. Objectives: The present study aimed to assess the efficacy of mindfulness-based cognitive therapy on the improvement of cognitive emotion regulation and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our electronic search strategy identified 5686 citations, of which 27 trials met the eligibility criteria (Figure 1). We included 1 additional trial identified through hand searching. One trial by Compen et al randomized patients to in-person MBCT, internet-based MBCT, and usual care cohorts and thus represented 2 separate analyses, for an overall total of 29 mindfulness-based comparisons (3053 participants).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our electronic search strategy identified 5686 citations, of which 27 trials met the eligibility criteria (Figure 1). We included 1 additional trial identified through hand searching. One trial by Compen et al randomized patients to in-person MBCT, internet-based MBCT, and usual care cohorts and thus represented 2 separate analyses, for an overall total of 29 mindfulness-based comparisons (3053 participants).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Many patients with cancer use mindfulness to manage anxiety, depression, and emotional distress during and after their cancer treatment. [15][16][17][18][19] Several randomized clinical trials (RCTs) conducted during the past decade [18][19][20][21][22] have examined the effect of mindfulness-based interventions on anxiety, depression, psychological distress, and HRQoL in adults with cancer. The results of these trials are conflicting about the effect of mindfulness on anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in the article “Predictors and moderators of outcomes in MBCT intervention for early breast cancer patients” ( 45 ), the authors aimed to discover the predictors and moderators of outcomes in MBCT for early breast cancer patients and explore the optimal course of treatment that produces significant outcomes ( 45 ). It can be argued that the role of MBCT in the treatment of breast cancer is now becoming clearer and represents a vital milestone in the palliative care of breast cancer patients ( 46 ). Similarly, CBT has also played a significant role in the treatment of other cancers, such as ovarian and prostate cancers, colorectal cancer and others ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%